Depopulation in the Puna: Effects of climate change and other factors - Alata, Eyner (2018)
Precisely establishing the context in which adaptation to climate change is occurring is very important, as it allows us to identify factors beyond the ecological. In fieldwork conducted in two communities in the Cordillera Blanca, Canray Grande and Los Andes Recuay, we have identified population loss in the puna. In sectors where before (1970s/80s) there were ten or more families, there are now only three families. To understand the reasons or causes of this population loss, we used ethnographic fieldwork, which revealed that this decline is due to factors beyond climate change.We attribute this population loss to demographic characteristics specific to these families in the puna, such as their lifecycles, which propagate the abandonment of the puna. Pastoral families use livestock as an asset, initially as a form of accumulation, and later as a form of consolidation. However, as families age, the number of animals they own declines and they abandon the puna. Concurrently, new generations view herding as a poverty trap, and as very demanding work, therefore orienting themselves towards wage-earning activities outside of the puna.